2000
DOI: 10.1021/ma991636h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Architecture on the Micellization Properties of Block Copolymers:  A2B Miktoarm Stars vs AB Diblocks

Abstract: Light-scattering and viscometric results are presented from micellar solutions of (PI)2PS (I2S) and (PS)2PI (S2I) three-miktoarm stars and a PSPI (SI) diblock copolymer in n-decane. The influence of architecture on the micellization properties of simple graft copolymers is investigated by keeping the overall molecular weights and compositions of the samples constant. All samples formed spherical micelles in n-decane, a selective solvent for polyisoprene. Aggregation numbers were found to increase in the order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
208
2
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(227 citation statements)
references
References 24 publications
16
208
2
1
Order By: Relevance
“…[1][2][3] It has been well-established that the topological structures and chemical composition of nonlinearshaped block copolymers can exhibit dramatic effects on the solution properties and self-assembling morphologies as compared with their linear counterpart. [4][5][6][7][8][9] It is worthy of noting that the developments of a variety of controlled radical polymerization techniques 10 such as atom transfer radical polymerization (ATRP), [11][12][13] reversible addition-fragmentation chain transfer (RAFT) polymerization, [14][15][16] and nitroxide-mediated polymerization (NMP) 17,18 have facilitated the synthesis of nonlinear-shaped polymers with varying chain architectures such as cyclic, 8,9,[19][20][21][22][23] (miktoarm) star, [24][25][26] star block copolymers, 27,28 comb, [29][30][31][32] sun-shaped, [33][34][35] H-shaped, [36][37][38] and θ-shaped 39,40 polymers. Among these nonlinear chain topologies, tadpole-shaped linearcyclic diblock copolymers [41]…”
Section: ' Introductionmentioning
confidence: 99%
“…[1][2][3] It has been well-established that the topological structures and chemical composition of nonlinearshaped block copolymers can exhibit dramatic effects on the solution properties and self-assembling morphologies as compared with their linear counterpart. [4][5][6][7][8][9] It is worthy of noting that the developments of a variety of controlled radical polymerization techniques 10 such as atom transfer radical polymerization (ATRP), [11][12][13] reversible addition-fragmentation chain transfer (RAFT) polymerization, [14][15][16] and nitroxide-mediated polymerization (NMP) 17,18 have facilitated the synthesis of nonlinear-shaped polymers with varying chain architectures such as cyclic, 8,9,[19][20][21][22][23] (miktoarm) star, [24][25][26] star block copolymers, 27,28 comb, [29][30][31][32] sun-shaped, [33][34][35] H-shaped, [36][37][38] and θ-shaped 39,40 polymers. Among these nonlinear chain topologies, tadpole-shaped linearcyclic diblock copolymers [41]…”
Section: ' Introductionmentioning
confidence: 99%
“…It is water-insoluble at neutral or alkaline pH, whereas below pH 6, it is soluble as a weak cationic polyelectrolyte due to protonation of tertiary amine residues. [35][36][37][38][39] Thus, we can expect that the copolymer, P(NIPAAm 85 -co-DEAEMA 140 ),…”
Section: Schizophrenic" Aggregation Of P(nipaam 85 -Co-deaema 140 mentioning
confidence: 99%
“…Other reports have also suggested that miktoarm polymers self-assemble differently from their linear counterparts. 144,145 Gou et al have reported the synthesis and drug loading of ibuprofenconjugated amphiphilic A 14 B 7 miktoarm stars composed of 14 PCL arms and 7 PEG arms with b-cyclodextrin (b-CD) as a core moiety. 146 These amphiphilic star polymers selfassembled into multimorphological aggregates in aqueous solution and showed higher drug loading capacity compared to the corresponding non-drug conjugated copolymers.…”
Section: Drug Loading By Physical Incorporationmentioning
confidence: 99%